Practical research on the boundaries of MAYA design principles with ceramic products as the carrier - Qi Wu; Mohd Faiz bin Yahaya; Lichen Tai; Qianhui Ren (PLoS ONE, 2026)
Both typicality and novelty shape aesthetic preference—typicality as conformity to a product’s prototype, and novelty as perceived difference and originality. While prior research has highlighted the tension and balance between these two factors, few studies have examined how product category structure moderates their effects. This study aims to investigate the roles of typicality and novelty in shaping consumer preferences, as well as whether product type (poor vs. rich categories) influences the relative impact of these factors. To achieve this, we conducted a within-subjects experiment using 20 ceramic product stimuli: 10 ceramic vases(poor categories) and 10 ceramic lighting items (rich categories). A total of 200 Chinese participants evaluated the typicality, novelty, and liking of each product using 7-point Likert scales. Data were analyzed using repeated-measures ANOVA, partial correlation, generalized estimating equations (GEE), and hierarchical regression. Findings revealed that typicality was more predictive in poor categories, while novelty played a greater role in rich categories. Moreover, product category structure significantly moderated these effects, confirming and refining the boundary conditions of the MAYA (Most Advanced Yet Acceptable) principle. Furthermore, regression analyses revealed that typicality and novelty together explained 21.8% of the variance in aesthetic preference for ceramic vases and 20.3% for ceramic lighting items. This research deepens theoretical understanding of aesthetic judgment by highlighting the contextual role of category structure. It also provides practical design guidance, emphasizing typical features in poor categories and prioritizing novelty in rich categories to optimize consumer appeal.